Journal of the Royal Statistical Society. Series C. Applied statistics - Friel, N.; Illian, Janine; Royal Statistical Society (Great Britain) (Oxford University Press, 2023)
'Series C' is a journal of international repute for statisticians both inside and outside the academic world.
Keywords: Statistics : Methodology : Periodicals; Statistics : Case studies : Periodicals